LAND ACQUISITION FOR ROAD CONSTRUCTION CASE STUDY: MAMMINASATA - SOUTH SULAWESI PROVINCE - , ALDILA REVIKA AKBAR; , Ir. Leksono Probo Subano MURP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traffic Congestion of the Mamminasata Region area is becoming worse year by year. The government has made efforts to improve the urban traffic conditions by taking various measures including development of roads and intersection. With the further population increase, the traffic congestion in Mamminasata and its surrounding was expected to be extremely serious in near the future. On the other hand, widening and new construction of roads were difficult due to land acquisition. If we identify the land acquisition mechanism, we can solve land acquisition problem. It is found that there are three types of mechanisms to completing land acquisition problem, namely